AKIBAT HUKUM PEMBAYARAN KLAIM YANG TIDAK SESUAI DENGAN NILAI YANG TERCANTUM DI DALAM POLIS ASURANSI JIWA - NIM. A1012201116, APRIANDI NYIPA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Claims are a form of responsibility from the insurance company as the guarantor of the insured if they experience a disaster such as death, where the insurance money is given to the heirs who are entitled to receive it. However, in reality, the payment of life insurance claims by insurance companies to the heirs of insurance policy holders who die does not match the value stated in the life insurance policy. Case of payment of life insurance claims by PT. BCA Life Pontianak Branch regarding the heirs of insurance policy holders who did not match the value stated in the life insurance policy was experienced by DV, JD, and PN as the heirs of AN as the policy holder/insured who died. This incident of course has legal consequences for PT. BCA Life Pontianak Branch against DV, JD, and PN as the heirs of policy holder AN who died in the event that the claim payment did not match the value stated in the life insurance policy because it caused losses for DV, JD, and PN as the heirs.The problem formulation in this research is: